2014
DOI: 10.1016/j.concog.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Synaesthesia in Chinese characters: The role of radical function and position

Abstract: Grapheme-colour synaesthetes experience unusual colour percepts when they encounter letters and/or digits. Studies of English-speaking grapheme-colour synaesthetes have shown that synaesthetic colours are sometimes triggered by rulebased linguistic mechanisms (e.g., B might be blue). In contrast, little is known about synaesthesia in logographic languages such as Chinese. The current study shows the mechanisms by which synaesthetic speakers of Chinese colour their language. One hypothesis is that Chinese chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that many of the coloured hearing synaesthetes were actually grapheme-colour synaesthetes (Baron-Cohen et al, 1993;. Although Chinese characters can also induce coloured sensation (Simner et al, 2011;Hung et al, 2014), the low graphemephoneme correspondence in Chinese characters can ensure that any mappings found in our study can be attributed to actual speech sounds instead of the writing system. Unlike in mainland China where all students learn the official pinyin system for Mandarin, Cantonese speakers in Hong Kong (i.e., participants in the current study) are not taught any Romanization methods for Cantonese at all.…”
Section: The Present Studymentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have shown that many of the coloured hearing synaesthetes were actually grapheme-colour synaesthetes (Baron-Cohen et al, 1993;. Although Chinese characters can also induce coloured sensation (Simner et al, 2011;Hung et al, 2014), the low graphemephoneme correspondence in Chinese characters can ensure that any mappings found in our study can be attributed to actual speech sounds instead of the writing system. Unlike in mainland China where all students learn the official pinyin system for Mandarin, Cantonese speakers in Hong Kong (i.e., participants in the current study) are not taught any Romanization methods for Cantonese at all.…”
Section: The Present Studymentioning
confidence: 54%
“…A robust pitch effect is observed with a high tone eliciting lighter colours and a low tone eliciting darker colours in general. To the best of our knowledge, this was the first study on vowelcolour association involving Chinese (tone language) speakers (Simner et al, 2011;Hung et al, 2014 were on grapheme-colour association) and using pitch difference produced by the same voice. Our results confirm the universality of this cross-modal association by extending the findings to new languages.…”
Section: Discussionmentioning
confidence: 99%
“…As is generally the case for literature on grapheme-color synesthesia, the search for the determinants of synesthetic color has been pursued mostly by testing synesthetes whose first language is English. Only a handful of studies have been conducted on grapheme-color synesthetes who experience colors with nonEnglish languages such as German (Emrich et al, 2004), Hebrew (Cohen-Kadosh et al, 2007), Korean (Kim and Kim, 2009), and Chinese (Hung, 2013;Hung et al, 2013;Simner et al, 2011). There are also few studies of English-speaking grapheme-color synesthetes who also experience colors with characters of multiple different languages such as Irish Gaelic, French, German, Italian (Barnett et al, 2009), Greek (Rich et al, 2005), Russian (Mills et al, 2002;Witthoft and Winawer, 2006), and Chinese (Hung, 2013;Ramachandran and Hubbard, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…the language has an opaque writing system, or many people learn non-native second languages in their childhood). However, it has not been investigated whether synaesthetic colours can be updated when new knowledge about graphemes is acquired; rather, it is usually emphasized that synaesthetes are highly consistent over time in their grapheme-colour associations [34,35]. As noted above, various features of graphemes can affect synesthetic grapheme-colour associations.…”
Section: Introductionmentioning
confidence: 99%